Study of various types of rice field management systems on the functional properties of rice - Ariyantoro Achmad Ridwan; Atmaka Windi; Sonata Belinda; Syamsiyah Jauhari (BIO Web of Conferences)
The purpose of this study was to investigate how various rice field management strategies affected the Mentik Wangi and IR64 white rice (Oryza sativa L.) varieties’ physical, chemical, physicochemical, functional, and sensory qualities. With just one factor—the conventional, semi-organic, and organic rice field management systems—the methodology applied a fully randomized design. The One Way ANOVA test and the DMRT test were employed for data analysis, with a 5% significance level. The analysis’s findings demonstrated that the rise in white degree value and thousand-grain weight was substantially impacted by the semi-organic rice field management system. Additionally, it improved both kinds’ solubility and swelling power. Meanwhile, because it is preferable as far as of color, appearance, and overall quality, the organic rice field management system greatly enhances the sensory experience. Conversely, the conventional rice field management approach on Mentik Wangi and IR64 rice raised the protein content (%db) and amylose content of all kinds.